FEATURES OF ADAPTIVE MANAGEMENT OF SOCIAL CONFLICTS IN PUBLIC POWER - STADNIYCHUK, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the features of adaptive management of social conflicts in public power. Conflicts are unavoidable and can be constructive or destructive. Thus, conflict management is a major part of practice, and especially managers and managers spend a lot of time preventing and intervening in conflicts of all kinds. The method of conflict management reflects key elements of organizational culture or socially general norms and is called the culture of organizational conflict in public powerSocial conflict can be understood by using the following synonyms: clash, tension, crisis, struggle, or friction. Although these words themselves are inadequate, in providing an acceptable definition, they are a repeating decimal part of a typical conflict. It is important to note that active conflict detection as a means of obtaining information requires a reasonable approach, as this can provoke an undesirable escalation of the conflict.Therefore, it is necessary to implement appropriate comprehensive procedures for mitigating the consequences of social conflicts. Conflict management should be adapted to specific conditions. Conclusion dilemmas inherent in the process of assessing the impact and participation of the public, such as the paradox of public participation and the problem of public goods, require new approaches to conflict management. Proactive conflict management, which includes early information about stakeholder attitudes as a potential limitation and early consideration of long-term benefits depending on the type of interaction, can be useful. Moreover, it may be useful to change views on the properties of social conflicts: an interested attitude to conflict situations, considering them as a valuable source of information, can create opportunities for new solutions to complex problems in public power.
Keywords: features; adaptive management; social conflicts; public power